PERANAN SEKTOR PERTANIAN DALAM PEMBANGUNAN WILAYAH KABUPATEN SIMALUNGUN PROVINSI SUMATERA UTARA - Elvin Desi Martauli; Rufti Puji Astuti (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2021)
The role of the agricultural sector in the regional development of Simalungun Regency, North Sumatra Province. The purpose of this study was to analyze the role of the agricultural sector in regional development in Simalungun Regency, North Sumatra Province. The data in this study were obtained from the Central Statistics Agency of Simalungun Regency and the Central Statistics Agency of North Sumatra Province from 2015-2019. The results showed that based on the value of the Gross Regional Domestic Product (PDRB), it can be seen from the economic growth in the region. When viewed from the PDRB of Simalungun Regency in the agriculture, forestry and fisheries sectors, it has the potential to be developed. The GDP contribution of the fisheries sector was 48.67 percent with a growth rate of 7.32. Based on the results of the LQ analysis, the agricultural sector in Simalungun Regency is a basic or superior sector with a contribution of 3.44 followed by Water Supply, Waste Management, Waste and Recycling of 1.12 and Wholesale and Retail Trade, and Car and Motorcycle Repair 1.09. As for the crop and vegetable horticulture agricultural sector commodity that contributed, namely cabbage with a harvest area of 2,406 hectares (21.50%). Of the food crops, namely lowland rice and oil palm, are plantation commodities with the highest production reaching 555,551 tons (97.76%).